2019
DOI: 10.3390/cancers11050589
|View full text |Cite
|
Sign up to set email alerts
|

A Protective Role of Aryl Hydrocarbon Receptor Repressor in Inflammation and Tumor Growth

Abstract: The aryl hydrocarbon receptor (AhR) is known for mediating the toxicity of environmental pollutants such as dioxins and numerous dioxin-like compounds, and is associated with the promotion of various malignancies, including lymphoma. The aryl hydrocarbon receptor repressor (AhRR), a ligand-independent, transcriptionally inactive AhR-like protein is known to repress AhR signaling through its ability to compete with the AhR for dimerization with the AhR nuclear translocator (ARNT). While AhRR effectively blocks … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 52 publications
1
31
0
Order By: Relevance
“…The results suggest that AhRR overexpression in the host environment is sufficient to inhibit orthotopic growth of mammary tumor cells. This builds on our prior study in which we demonstrated that growth of lymphoma cells was suppressed in AhRR Tg mice (42). We note that the growth of E0771 cells was suppressed in untreated AhRR transgenic mice suggesting that AhRR overexpression in the host may suppress tumor growth independent of exogenous and toxic AhR ligands.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…The results suggest that AhRR overexpression in the host environment is sufficient to inhibit orthotopic growth of mammary tumor cells. This builds on our prior study in which we demonstrated that growth of lymphoma cells was suppressed in AhRR Tg mice (42). We note that the growth of E0771 cells was suppressed in untreated AhRR transgenic mice suggesting that AhRR overexpression in the host may suppress tumor growth independent of exogenous and toxic AhR ligands.…”
Section: Discussionsupporting
confidence: 71%
“…The results are in line with the in vivo findings and confirm previous reports showing a reduced cell proliferation, increased apoptosis and inhibition of inflammatory invasion and migration of breast cancer cells by AhRR overexpression ( 1 , 8 , 17 , 37 ). Our previous studies found that C/EBPβ and COX-2 are important mediators of an AhR-dependent and TCDD-induced resistance to apoptosis in lymphoma cells, demonstrating their critical role in AhR-driven tumor cell survival ( 42 , 51 ). In addition to a host-dependent tumor suppressive effect of AhRR indicated by current data from a mouse xenograft model, the results with mammary tumor cells suggest that AhRR mediates also cell-intrinsic responses associated with the suppression of C/EBPβ and COX-2.…”
Section: Discussionmentioning
confidence: 98%
“…Although AHR expression levels do not differ significantly in various types of skin cancer ( Figure 3 A), we observed a significant downregulation of AHRR expression in skin cutaneous melanoma (SKCN) ( Figure 3 B). Vogel et al report that the upregulated AhRR expression inhibits the AhR-mediated antiapoptotic response in mouse embryonic fibroblasts [ 206 ]. As AhRR tends to play a significant role in suppressing inflammation, the downregulated AHRR expression may promote tumor growth.…”
Section: The Role Of Tryptophan-derived Ahr Ligands In Skin Homeosmentioning
confidence: 99%
“…Thus, the AhRR is an AhR competitor in that it may form the heterodimeric AhRR/ARNT complex, which binds to the XRE, and consequently repress the transcription. The AhRR effects mediate key processes such as inflammation and tumor growth that have led to its consideration as a drug target [ 47 , 48 ]. The repression pathway is also controlled by the receptor itself and its transcriptional outcomes forming a regulatory circuit [ 49 ].…”
Section: Aryl Hydrocarbon Receptormentioning
confidence: 99%